The role of Leishmania proteophosphoglycans in sand fly transmission and infection of the mammalian host. - Rogers, Matthew E. (Frontiers in Microbiology, 2012)
Leishmania are transmitted by the bite of their sand fly vector and this has a significant influence on the virulence of the resulting infection. From our studies into the interaction between parasite, vector and host we have uncovered an important missing ingredient during Leishmania transmission. Leishmania actively adapt their sand fly hosts into efficient vectors by secreting Promastigote Secretory Gel (PSG), a mucin-like gel which accumulates in sand fly gut and mouthparts. This has the effect of blocking the fly, such that during bloodfeeding both parasites and gel are co-transmitted in an act of regurgitation. We are discovering that this has further implications for the mammalian infection, again, in favour of the parasite. Experimentally, PSG exacerbates cutaneous and visceral leishmaniasis and can promote the chronicity of Leishmania infection, even in mouse strains normally capable of controlling leishmaniasis. The underlying mechanism of PSG’s action is a major focus of our ongoing work. This review aims to synthesise what is known about the role and action of PSG and its constituent proteophosphoglycans, for parasite colonisation of the sand fly, transmission and mammalian infection. Lastly, we discuss potential exploitation of this important vector-derived product and future avenues of research.